2021
DOI: 10.1002/aoc.6268
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spin Seebeck effect of reverse spin crossover Fe (II) micellar charge transport using PMMA polymer electrolyte

Abstract: The electrochemical thermoelectric effect is capable of generating Seebeck and conductivity from a temperature gradient through redox reaction at the electrode. Conventional spin Seebeck effect (SSE) is the generation of spin voltage by solid coupling magnetic thin film in presence of magnetic field and temperature gradient. In this study, we demonstrate an enhancement of a magnetic free SSE of Fe (II) reverse spin-crossover in electrolyte using 1% PMMA polymer additive in form of polymer electrolyte. The reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…[ 8,17–19 ] The thermopower of i‐TE materials is derived from the mobility difference of cations and anions driven by the temperature gradient or the redox reactions of ion pairs (e.g., Fe(CN) 6 4− /Fe(CN) 6 3− ) near electrodes at different temperatures. [ 20,21 ] Therefore, there is no obvious coupling relationships among the foregoing parameters of i‐TE materials. It is more likely to realize a higher thermoelectric conversion efficiency for i‐TE generators than e‐TE generators through rational designs of materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,17–19 ] The thermopower of i‐TE materials is derived from the mobility difference of cations and anions driven by the temperature gradient or the redox reactions of ion pairs (e.g., Fe(CN) 6 4− /Fe(CN) 6 3− ) near electrodes at different temperatures. [ 20,21 ] Therefore, there is no obvious coupling relationships among the foregoing parameters of i‐TE materials. It is more likely to realize a higher thermoelectric conversion efficiency for i‐TE generators than e‐TE generators through rational designs of materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…The spin Seebeck effect that has occurred after the spin state transition contributed to the high charge transport properties. 5 During these occurrences, the potential in the thermal sensor increased dramatically. As a result, high cell power density is obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Megat Hasnan et al has reported that SSE of polymer-based electrolyte in a thermoelectrochemical cell study has induced the spin S e and can act as a thermal booster to enhance ionic mobility and diffusivity. 5 Besides that, the spin state transition can cause two other effects such as the kosmotropic and chaotropic effect. The kosmotropic effect (inducing structure) is the ordered structure of complexes by stabilizing intramolecular interactions between Fe–ligand, whilst the chaotropic effect (inducing disorder) produces the opposite effect by disrupting and destabilizing the complex structure.…”
Section: Introductionmentioning
confidence: 99%